High prevalence of extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae isolates: A 5-year retrospective study at a Tertiary Hospital in Northern Thailand - Siriphap, Achiraya; Kitti, Thawatchai; Khuekankaew, Akachai; Boonlao, Chalermchai; Thephinlap, Chonthida; Thepmalee, Chutamas; Suwannasom, Nittiya; Khoothiam, Krissana (Frontiers in Cellular and Infection Microbiology, 2022)
Background: The global emergence and spread of extended-spectrum beta-lactamase (ESBL)-producing Enterobacterales, especially Escherichia coli and Klebsiella pneumoniae, have been recognized as a public health concern as severe infections caused by these microorganisms increase morbidity and mortality. This study aimed to assess the prevalence of ESBL-positive E. coli and K. pneumoniae strains isolated from hospitalized patients in Chiangrai Prachanukroh hospital, Chiangrai province, Thailand. Methods: This retrospective analysis was conducted from January 2016 to December 2020. A total of 384,001 clinical specimens were collected aseptically and further cultivated on an appropriate medium. All clinical isolates (one isolate per patient) were identified based on standard laboratory methods. Antibiotic susceptibility testing was performed by the Kirby Bauer disc diffusion technique following CLSI guidelines. ESBL production was screened with ceftazidime and cefotaxime discs based on the CLSI recommendations. Phenotypic confirmation of ESBL production was carried out using a double-disc synergy technique following the CLSI standard. Results: Of a total of 384,001 clinical samples analyzed for bacterial species identification, 11,065 (2.9%) tested positive for E. coli and 5,617 (1.5%) for K. pneumoniae. Approximately 42.5% (4,706/11,065) of E. coli and 30.2% (1,697/5,617) of K. pneumoniae isolates were classified as ESBL producers. A higher proportion of ESBL producers was found in patients older than 60 years and male groups. The highest infection rates of ESBL-positive pathogens were observed among patients in a medical unit. ESBL-producing E. coli and K. pneumoniae isolates were predominantly found in urine and sputum, respectively. ESBL producers exhibited a high resistance rate to ampicillin (99.8–100%), cefazolin (100%), cefotaxime (100%), fluoroquinolones, and trimethoprim/ sulfamethoxazole. Conclusions: This study demonstrated the high prevalence and emerging antibiotic resistance of ESBL-positive E. coli and K. pneumoniae isolates from patients admitted to a provincial hospital in northern Thailand. Most ESBL-producing strains were highly resistant to several antimicrobial agents apart from carbapenems and aminoglycosides These findings indicated that carbapenems and aminoglycosides should be advised as the first-line drugs of choice for serious infections with ESBL-producing Enterobacterales.